Phytochemical Screening and Free Radical Scavenging Activity of Different Extraction Solvent Polarity of Euphorbia hirta L. - Teng Ming Qing; Mohamad Haziq Norsam; Kori Muhammad Alkali; Ahmad Arif Ismail; Pa'ee, Furzani (Journal of Sustainable Natural Resources, 2026)
Euphorbia hirta is one of the alternative or traditional medicines which are now being used more often to treat a wide range of diseases such as intestinal parasites, diarrhoea, peptic ulcers and asthma by using decoction or infusion. The objective of this study is to evaluate the efficiency of polar and non-polar solvent effects on the determination of total flavonoid content and free radical scavenging activity and test the phytochemical properties (phenolic and flavonoid) in Euphorbia hirta and DPPH free radical scavenging activities of flavonoids extracted from different solvents of extraction. Extraction with higher-polarity solvents resulted in substantially higher yields, with ethanol achieving 22.46% compared to only 3.37% for ethyl acetate. Phytochemical screening of ethanol extracts showed the presence of phenolics and flavonoid compounds, but only the phenolic compound showed in the ethyl acetate extract. The value of total flavonoid content is 34.3556 ± 19.0346 mg of quercetin/g extract for ethanol extract, which has higher total flavonoid content compared to ethyl acetate extract, which is 7.6340 ± 1.9363 mg of quercetin/g extract. Ethanol extract demonstrated greater scavenging activity based on IC50 values, which it is 0.520281 ± 3.182 µg/ml compare to ethyl acetate extract which has a 43.6095 ± 32.1432 µg/ml IC50 value. The study suggests that E.hirta has high total flavonoid content and low IC50 value, and ethanol extract is a great solvent to use for further development of the plant’s products or illness cure.